Bronchopulmonary Dysplasia in Post-Surfactant Era: Results of an Objective Assessment of the Disease - I. V. Davydova; A. V. Anikin; O. V. Kustova; A. V. Sidenko; E. Yu. Basargina; E. V. Pavlyukova; V. K. Pozharishchenskaya (Вопросы современной педиатрии, 2015)
Modern methods of respiratory support have led to the transformation of the course of bronchopulmonary dysplasia. A significant role is played by the use of surfactant preparations for the prevention of respiratory distress syndrome and subsequent formation of bronchopulmonary dysplasia in premature infants. In this connection, an objective assessment of the efficacy of surfactant replacement therapy is required. The article presents the results of studying the patterns of development of bronchopulmonary dysplasia in premature infants (n =121) of different gestational age. It was shown that a new form of moderate or mild bronchopulmonary dysplasia prevailed in extremely premature infants in the course of surfactant replacement therapy. Children of a gestational age greater than 32 weeks who do not require surfactant therapy usually have typical bronchopulmonary dysplasia.